Physiology of salt stress in plants : perception, signalling, omics and tolerance mechanism - Singh, Pratibha (Plant physiology); Singh, Madhulika; Singh, Rajiv Kumar (Hoboken, NJ : Wiley, 2022)
'This book extensively covers the problem of soil salinity in modern agricultural practices, and social and environmental issues pertaining to them. The impact of salt on soil microorganisms, crops and other plants is presented along with the impact on other organisms including aquatic fauna, terrestrial animals and human beings. The dimensions of the impact are morphological, anatomical, physiological and biochemical. Physiology of Salt Stress in Plants will allow social scientists and environmentalists to think more logically. Additionally, plant and environmental scientists may get ideas to promote less hazardous fertilizer and pesticides, to use their safer doses, to explore and work upon salt resistant varieties of plants'--
Includes bibliographical references and index.
Keywords: Crops -- Effect of salt on; Plants -- Effect of salt on; Crops -- Effect of stress on; Plants -- Effect of stress on; Soils, Salts in